Deciphering the Redox Chain Mechanism in the Catalytic Alkylation of Quinones - Xu, Xiao-Long; Li, Zhi (Synlett, 2018)
Alkylation of p-quinones with allylic and benzylic esters is achieved by using a strong Lewis acid as the catalyst. This transformation likely follows an unusual redox chain mechanism. In this mechanism, quinone undergoes a sequence of reactions: it is reduced to hydroquinone (HQ), functionalized in a Lewis acid-catalyzed Friedel–Crafts alkylation, and then oxidized back to quinone. The last step is concurrent with the first step of a second quinone molecule, which is reduced to new HQ and functionalized, and thus propagates the redox chain reaction. The autoinitiation mechanism of the redox chain is not well understood, but additive HQ or Hantzsch ester can serve as effective initiators. The likelihood of this mechanism was elaborated by kinetic studies and various control experiments.1 Introduction2 Discovery of Catalytic Alkylation Reactions of Quinones3 Proposed Redox Chain Reaction Mechanism and Experimental Evidence4 Substrate Scope5 Conclusion
Keywords: quinones; C–H functionalization; Lewis acids; redox chain reaction